Autologous serum therapy: a viable option for chronic spontaneous urticaria - Sundaresh, Darshana; Kumaravel, S.; Anbumalar, M. (International Journal of Research in Dermatology, 2020)
Background: Chronic urticaria (CU) is a common disorder causing decrease in quality of life of patients with associated morbidity, chronic dependence on medications and a huge pill burden. CU is multifactorial and a subset of patients have an autoimmune background for their condition which is confirmed by a positive skin reaction to ASST. This study compared the efficacy of Autologous serum therapy in both ASST positive and ASST negative patients by evaluating total severity score (TSS). Methods: This quasi experimental study was conducted on fifty patients were selected randomly and withdrawn from antihistaminic use. ASST was done for all patients and AST was administered to all patients in both groups for 9 weeks. The patients were followed up at 4 weeks and 12 weeks after completion of AST. TSS measurements were used as baseline and recorded weekly after each injections till 9 weeks then 4th and 12th week after completion of therapy. Results: 50 patients were the study population. The median age was 34.7 years with a female predominance. 23 patients were ASST positive and the rest were negative. Following treatment, ASST positive group had 69% improvement in TSS and ASST negative group had 61.5% improvement in TSS. There was statistically significant differences following treatment compared to baseline and between the two groups. Conclusions: AST as an adjunctive treatment for chronic urticaria shows promise for patients irrespective of ASST positivity and is more effective for ASST positive patients.